Translation, cross-cultural adaptation, and psychometric validation of the Malay version of the Assessment of Quality of Life-6 Dimensions (Malay-AQoL-6D) instrument among Malaysians living with chronic heart failure - Yi Jing Tan; Siew Chin Ong; Sook Pin Goh; Gang Chen; Vee Sim Yong; Wei Wern Khor; Ying Min Kan; Yong Ying Choong; Ainul Mardhiyyah Zameram; Lin Yuing Tan; James Yau Hon Voo; Kar Kei Lam; et al. (SpringerOpen, 2024)
Abstract Background This study aimed to translate and culturally adapt the Assessment of Quality of Life (AQoL)-6D into Malay (Malay-AQoL-6D), and assesses the instrument's acceptability, reliability, and validity among Malaysians living with chronic heart failure (HF). Methods The translation and cross-cultural adaptation process adhered to international guidelines. The Malay-AQoL-6D underwent content and face validity assessments via expert review, and pretesting among healthy individuals and patients with chronic conditions. Subsequent psychometric validation utilised clinico-sociodemographic data and paired AQoL-6D and EQ-5D-5L data from a health-related quality-of-life (HRQoL) survey involving Malay-speaking patients with HF, which encompassed assessments of Malay-AQoL-6D acceptability, internal consistency and test-retest reliability, as well as its construct, concurrent, convergent and divergent, and known-group validity. Results The Malay-AQoL-6D was deemed acceptable among clinicians and local patients, achieving a 90.8% completion rate among 314 patients surveyed. The instrument demonstrated strong content validity (item-level content validity index [CVI]: 0.83-1.00, average CVI: 0.98), internal consistency (Cronbach's alpha: 0.72-0.89; MacDonald's omega: 0.82-0.90, excluding the Senses dimension), and test-retest reliability (average intraclass correlation coefficients: 0.79-0.95). Confirmatory factor analysis confirmed the instrument's two-level, six-factor structure (Satorra-Bentler [SB]-scaled χ2(df: 164): 283.67, p-value < 0.001; root mean square error of approximation [RMSEA]: 0.051; comparative fix index [CFI]: 0.945, Tucker-Lewis index [TLI]: 0.937; standardised root mean-squared error [SRMR]: 0.058). The Malay-AQoL-6D's concurrent validity was evident through its good agreement with EQ-5D-5L. Multiple hypothesis tests further affirmed its construct and known-group validity. The Malay-AQoL-6D's psychometric properties remained consistent across different missing data techniques. Conclusion The findings suggest that Malay-AQoL-6D could be a culturally acceptable, reliable, and valid HRQoL measure for quantifying HRQoL among the local HF population. Future studies are necessary to further validate the instrument against other measures and confirm the instrument's test-retest reliability and responsiveness, which are possible with the availability of the Malay-AQoL-6D.